Factors that affect the purchase decision of proton car in Pulau Pinang - Tang, Wei Chau (2018)
The objective of this research is to examine the factors that affect the purchase decision of PROTON car in Pulau Pinang. This research uses mall intercept method to collected data from respondents. The population of respondents in Pulau Pinang is around 1.767 million. Thus, the sample size in this research is 3 84 respondents according to the Krejcie and Morgan table (1970). However, 400 sets of questionnaires were successfully collected through the data collection. Through review of literature and previous studies, a conceptual model was defined and the variables affect the purchase decision of PROTON car included the brand image, quality, design or aesthetic and price. In this study, SmartPLS was used to analyze the measurement and structural models. By using SmartPLS, the data was transformed into Excel CVS file to generate raw input for the application. The findings reveal that the purchase decision of PROTON car had positive relationship and significant with brand image, price and design or aesthetic. While the quality factor does not have a significant relationship with the purchase decision of Proton car.